Governança colaborativa em parques tecnológicos: estudo de casos em Minas Gerais - Costa, Hebe Andrade (2015)
In this work intended to identify how collaborative governance is manifested in installed technology parks or in installation process in Minas Gerais state from the Anselle Gash model (2007). This model consists of five theoretical constructs identified as necessary for good collaborative governance, which are: (i) a dialogue face to face; (ii) building trust; (iii) the commitment to the process; (iv) the shared understanding and (v) the intermediate results. The methodology adopted was the case study in two technology parks, one being implemented (Park 1) and other operating phase (Park 2). Interviews were conducted with representatives of different social actors involved in the parks (university, park manager, local government and installed company or pretend to be installed). Documents were also consulted (laws, brochures, websites, etc.) and it was held an observation with free notes. The data collected (transcribed interviews, documents and notes) constituted the corpus of analysis. It was held the material content analysis based on five theoretical analysis model constructs. The results showed that although some precepts of collaborative governance manifest in the two technology parks investigated, it is not possible affirm that it exists in fact, since the collaboration spaces are informal, and asymmetrical participation of the actors involved. At the same time, it notices that constructs of collaborative governance (although not known the actors) are legitimated as important to the success of the projects.